High-altitude precipitation controls the mass balance of Pasu Glacier, Karakoram over 2000-2020: a case study based on mass and energy budget - Zhu, Yu; Liu, Shi-Yin; Yi, Ying; Tian, Li-De; Ashraf, Muhammad; Xie, Fu-Ming; Saifullah, Muhammad; Ali, Syed Hammad; Grünwald, Richard (Advances in climate change research, 2025)
Glaciers in the Karakoram exhibit stability or near-balanced mass changes, in stark contrast to the widespread glacier retreat observed globally. However, the limited availability of observational data, coupled with the lack of in-depth exploration of ablation physical mechanisms, has hindered a comprehensive understanding of the factors driving the anomalous behavior of these glaciers. This study employs an energy‒mass balance model, validated against observational data, and focuses on the representative Pasu Glacier to identify the key factors contributing to the near-balanced glacier mass budget observed over 2000-2020. The analysis revealed an average mass balance of −0.030 ± 0.247 m w.e. per year for Pasu Glacier in 2000-2020, with an average equilibrium line altitude of 4150 m. While snowfall was the primary determinant of mass balance for interannual and seasonal variations, turbulent heat exchange also played a significant role in the glacier's energy balance process. Through an analysis of altitude gradients and long-term variations in mass‒energy gain and loss and comparisons with other glaciers in High Mountain Asia (HMA), we concluded that 1) the balanced state of Pasu Glacier was largely attributed to the magnitude and extent of the accumulation of precipitation at high elevations, 2) reduced snowfall in highly accumulated areas (−0.79% per year), increasing melting intensity (0.026 m w.e. per year), and prolonged melting duration (∼24 d during 2000-2020) indicated a negative tendency of glacier mass budgets, and 3) Pasu Glacier exhibited similar characteristics of continental glaciers in terms of energy balance and polar continental glaciers in terms of mass gain, which have contributed to the stability of Pasu Glacier in 2000-2020. Our findings provide valuable insight into the dominant factors contributing to the balanced state of Pasu Glacier and can be applied to addressing other glacier changes in the Karakoram.
Online verfügbar: 4. April 2025, Artikelversion: 29. Mai 2025
Gesehen am 08.12.2025